CMAS corrosion characteristics of YSZ and Al2O3-YSZ thermal barrier coatings at 1250 °C–1350 °C - Dou, Mengfan; Gao, Wei; Xue, Ting; Han, Jiasen; Wu, Dongting; Zou, Yong; Zhang, Yongang (Journal of the European Ceramic Society, 2024)
The calcium-magnesium-aluminum-silicate (CMAS) corrosion is now a great threat to thermal barrier coatings (TBCs), inducing coating spallation readily. The CMAS corrosion characteristics of both 7YSZ and 20 wt.%Al2O3-YSZ TBCs at a broad temperature range of 1250 °C to 1350 °C were investigated. 7YSZ coatings were completely degraded by CMAS at 1250 °C while the increased corrosion temperatures induced more serious destruction. This is due to that the viscosity of CMAS melt significantly decreased with corrosion temperature increasing, promoting melt fluidity and infiltration. The Al2O3-YSZ composite TBCs demonstrated superior resistance to CMAS corrosion at 1250°C-1350 °C. The intensive chemical reactions between Al2O3 and CMAS melt promoted the formation of anorthite products with either short rod-shaped or blocky morphologies. These products closely interconnected and stacked up to generate a dense layer, physically blocking CMAS melt infiltration and effectively improving the anti-CMAS corrosion properties of TBCs at higher temperatures. Furthermore, the corrosion temperatures critically influenced anorthite formation and present morphologies.